Penyuluhan Hukum Untuk Meningkatkan Kesadaran Tentang Bahaya Narkoba Dan Kekerasan Seksual Di Karang Taruna Desa Kebonsari Baru Jambangan – Surabaya - Ari Kosasih; Rafli Hamzan Aryaputra; Diva Faradhilla Ayu Amelia; Wahyu Fadhilla Akbar; Renalda Risdiyanti Putri (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
The problem of drug abuse and victims of sexual violence is something that has occurred in society from the past until now. Cases like this must be handled quickly because it is a case that causes a lot of victims who cannot be said to be in small numbers in the community. Actually in this case there is no target age desired by the perpetrator to carry out his actions in committing one of these criminal acts. As what is meant in this case is that there are still many children who are still minors who are the future generation of the nation in the future even become victims of drug abuse and sexual violence. Therefore, we should increase efforts to reduce or even stop cases like this. The community must also be careful of people they don't know to be aware of themselves so that they become victims of drugs and victims of sexual violence.